Efektifitas Terapi Kompres Jahe dan Kompres Serai Hangat untuk Menurunkan Intensitas Nyeri Arthritis Rheumatoid pada Lanjut Usia - Tina Yuli Fatmawati; Ariyanto Ariyanto (Universitas Baiturrahim, 2021)
Rheumatoid arthritis is one of the most common diseases in society and is one of the groups of diseases that is always found in the practice of general practitioners. this disease attacks the joints and some only attack the tissues around the joints. The purpose of this study is to find out whether there are differences in the treatment of ginger compresses and warm lemongrass compresses against the reduction in the intensity of Rheumatoid Arthritis Pain in the Elderly at Tresna Werdha Budi Luhur Social Home in Jambi. The research design used was Pre-Experiment using One Group Pre-Post Test Design. Research has been done at the Budi Luhur Werdha Home in Jambi (PSTW). The sampling method was by purposive sampling with a sample of 18 respondents with ginger compress intervention and 18 respondents with lemongrass intervention. Analysis data used univariate analysis and bivariate analysis with the Dependent T-Test. The results were no differences in the intervention of ginger compresses and warm lemongrass compresses to the intensity of rheumatoid arthritis pain in the elderly in PSTW Jambi City. Both of them have a p-value of 0,000, meaning they both have a significant effect on decreasing the intensity of arthritis rheumatoid pain in the elderly in PSTW. It is recommended for health workers, it should be able to continue to motivate the elderly by providing education and demonstration, especially regarding the handling of pain in a non-pharmacological way through alternative and complementary techniques.